The Urgency of Increasing Teacher Vocational Competence in the Era of Society 5.0 - Lili Suryati; Ambiyar Ambiyar; Ahyanuardi Ahyanuardi; Yulia Efronia; Sri Rahmadhani (Universitas Muhammadiyah Enrekang, 2023)
Increasing the competence of vocational education teachers is an urgent need. This will ensure that vocational education can provide maximum benefits for students and align with the dynamics of the ever-evolving world of work. Data was collected using systematic literature method. The results of the study show that the urgency of the vocational competence of teachers in the era of society era 5.0 is very important and studies are needed to improve it. Overall, the urgency of improving teacher vocational competence in the current era is closely related to preparing students to contribute to the changing world of work and improving the quality of vocational education as a whole. By increasing the qualifications and knowledge of teachers in the vocational field, we can ensure that the education provided matches the demands of the labor market and produces students who are ready for the future. Some of the skills that teachers must have in this era include digital skills, adaptive skills, critical and creative thinking skills, multicultural skills, skills in implementing Teaching Factory in the learning process, collaboration and emotional social skills. Society Era 5.0 provides significant benefits for the realm of vocational education. In this era, digital technologies such as artificial intelligence (AI) and the Internet of Things (IoT) can be used in the vocational learning process. Technology-based learning systems enable more interactive and realistic practical experiences, through simulation and virtualization. This shows that more efforts are being made to develop vocational teacher competencies, especially for vocational education concept competencies.